solve the equation
3x^(-1/2) - 4 = 0
I've moved this thread here to our algebra forum since this is a better fit given the question.
We are given to solve:
$ \displaystyle 3x^{-\frac{1}{2}}-4=0$
What do we get if we multiply through by $x^{\frac{1}{2}}\ne0$?
Well if we multiply through by $x^{\frac{1}{2}}$ we have:
$ \displaystyle 3x^{-\frac{1}{2}}x^{\frac{1}{2}}-4x^{\frac{1}{2}}=0x^{\frac{1}{2}}$
Now, for the first term on the left, we can use the following property of exponents:
$ \displaystyle a^{b}\cdot a^{c}=a^{b+c}$
So, what does this term become?